PENDAMPINGAN KIOS BUAH UCOK KOMPLEK MMTC JALAN PANCING MEDAN - Fauzia Agustini; Dita Amanah; Dedy Ansari Harahap (Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
The Ucok fruit stall located in the MMTC Complex, Jalan Pancing Medan, does not experience a significant increase in sales every year. Therefore, the author conducts coaching on this kiosk which aims to increase sales of this fruit kiosk continuously. The problems faced by the Ucok fruit kiosk are the very high level of competition, cleanliness, layout and the unavailability of simple financial reports. Through interviews, observations and literature studies, the authors have carried out a series of coaching activities such as adding new fruit types, making packaging for several fruits using foam nets/nets/nets as a product diversification step, always paying attention to the cleanliness of the kiosk, redesigning the layout preparation fruit starting from setting the color, size and type of fruit and make financial records in a simple way.